Review of the genus Siemssenius Weise, 1922 (Coleoptera: Chrysomelidae: Galerucinae) from Taiwan, with descriptions of five new species - Lee, Chi-Feng (Zootaxa, 2016)
Taiwanese species of Siemssenius are separated into two species groups, the S. metallipennis group and S. rufipennis group, based on color patterns and other morphological characters. Members of the S. rufipennis group cannot be distinguished using external morphology but may be diagnosed by distributions and genitalia morphologies. Seven species are recognized in Taiwan, including two previously described species, S. rufipennis (Chûjô, 1962) and S. metallipennis (Chûjô, 1962), and five new species, S. cheni Lee, sp. nov., S. jungchani Lee, sp. nov., S. liui Lee, sp. nov., S. tsoui Lee, sp. nov., and S. yuae Lee, sp. nov. Speciation models explaining the high diversity of Siemssenius species in Taiwan, are discussed.